Analisis dan Perancangan Aplikasi CRM Berbasiskan Web pada Lembaga Pendidikan Bahasa - Saputra, Lea Sulaiman (Bina Nusantara University, 2012)
The purpose of this paper is to design a web-based CRM applications in language education institutions to improve services to siswas. Expected use of these applications can help siswas in terms of providing ease of learning takes place during and after the learning process is completed. Methodology and approach used in this paper is analysis of literature study, interviews, survey results, and design. The results obtained is that the CRM application designed can be run well. The CRM application can support and assist both prospective siswas and siswas related to study programs, support the customer service of the involved language educational institution in developing relationships with both prospective members and members, and help promote the institution.